Non-surgical treatments for androgenetic alopecia: a literature review - Woźniak, Aleksander; Kozłowska, Martyna; Sydor, Patryk; Wartacz, Marcel; Kreft, Rafał; Hunek, Adrian Krzysztof; Bigdoń, Anna Maria; Ćwiek, Maciej; Gorczyca, Przemysław; Góra, Mateusz (Journal of Education, Health and Sport, 2023)
Androgenetic alopecia is the most common type of hair loss and affects at least 80% of men and half of women before the age of 70, with the incidence increasing with age. Androgenetic alopecia is an ailment conditioned by genetic and hormonal factors, associated with excessive stimulation of the androgen receptor in the cells of the hair follicle. With the development of medicine, more and more therapeutic methods for androgenetic alopecia appear on the market, including minoxidil, 5-α-reductase inhibitors, microneedling, platelet-rich plasma, low-energy laser therapy, rosemary oil, or siRNA. Thanks to the constantly growing amount of scientific research, progressively more is known about the mechanisms of androgenetic alopecia development and potential strategies to stop it. The article analyzes the literature using electronic databases and textbooks to compile methods that can be an effective alternative for people who do not want to undergo surgery. Some of the methods presented in the article have the potential to not only slow down, but also reverse the progression of the disease. However, each of them still has its limitations.